Report of the Army Scientific Advisory Panel Ad Hoc Group on Climatic Testing - Montgomery, Richard; Brock, Robert L; Clark, Kenneth E; Fadum, Ralph E; DeYoung, Clarence M (1976)
The report considers the need for testing under extreme environmental conditions. It concludes that climatic testing should be an integral part of the development process, using simulated facilities as well as natural environments. It recognizes a need to test all general-purpose equipment down to -25F, as well as test under extreme conditions under very selective criteria. The Arctic and Tropic Test Centers are examined and refocused missions are presented. The Arctic Test Center is considered an irreplaceable asset of primary utility for operational testing, especially under intermediate conditions. The Tropic Test Center is required and should be used for materials/component development testing. General observations of test management are presented.